Internet of things between reality or a wishing-list: a survey - Salem Alzboon, Mowafaq (International Journal of Engineering and Technology, 2019)
Internet of Things is considered to represent a platform in which daily devices and their processing get more intelligent than ever where daily communications get further informative. While the Internet of Things remains searching its particular shape, its influences have gazed in producing inconceivable steps as a universal solution media pertaining to the linked scenario. The architecture of particular research regularly controls the confirmation pertaining to the corresponding domain. The lack of the whole architectural knowledge is currently motivating researchers to obtain the scope related to Internet of Things centric methods. The literature reviews the Internet of Things oriented architectures, which can develop the comprehension of corresponding technology, method, and tool in order to ease the requirements related to a developer. Additionally, research issues are examined to integrate the lacuna within the present tendencies of particular architectures in order to inspire many organizations and academics to search for conceivable methods that are inconsistent with the precise robustness of Internet of Things. The major contribution related to this paper is based on summarizing the present state-of-the-art regarding the Internet of Things by highlight technical, sensing issues as well as the future direction toward.Â